The Equivalence of Datko and Lyapunov Properties for (h,k)-Trichotomic Linear Discrete-Time Systems - Claudia-Luminiţa Mihiţ; Mihail Megan; Traian Ceauşu (Discrete Dynamics in Nature and Society)
The aim of this paper is to characterize a general property of (h,k)-trichotomy through some Lyapunov functions for linear discrete-time systems in infinite dimensional spaces. Also, we apply the results to illustrate necessary and sufficient conditions for nonuniform exponential trichotomy and nonuniform polynomial trichotomy.